Les pratiques de responsabilité sociétale des acteurs touristiques en Guinée : Cas des PME de Grand Conakry (Guinée) - Moussa Fantagbè Kourouma; Mamadou Diombera (Études Caribéennes, 2024)
The tourism sector in Guinea is among those which contribute to the degradation of biodiversity, the environment and social values. Tourism is growing in sensitive areas such as coastal areas, waterfalls and historic sites. Tourist development and the construction of accommodation and leisure infrastructures have impacts such as the destruction of mangroves, forests and aquatic and terrestrial animal species. These consequences are felt with the reduction of certain plant and animal resources, global warming, atmospheric pollution, floods. Beyond the impacts on ecosystems, host communities sometimes lose their cultural identity to the benefit of practices such as pedophilia or sex tourism, in addition to difficult working conditions, etc. For all these reasons, tourist SMEs in Greater Conakry are concerned by good CSR practices as much as large tourist chains are required to respect tourism sustainability measures. This article diagnoses social responsibility practices in the context of SMEs in the Guinean tourism sector in order to promote sustainable tourism. Quantitative and qualitative methodological approach were used for data collection and analysis. Data collection was carried out using an interview guide, a reading grid and a questionnaire survey with kobocollect. The study thus led to the results: lack of mastery of the CSR concept; presence of certain CSR practices; lack of documentation of CSR actions; limits.